Effect of nitric acid on Rice Husk Ash steel fiber reinforced concrete. (2020) - Singh, Amrendra; Kumar, Rakesh; Mehta, P.K.; Tripathi, Deep
Abstract: Concrete is globally used construction material and nowadays its durability is the main concern. Acid is one of the chemicals influencing the durability of concrete. Nitric acid (HNO3 ) is one such acid. Several mineral admixtures are used to improve the durability of concrete. Rice Husk Ash (RHA) is one of such admixtures. This paper make known the results of an experimental programme intended to explore the durability aspects of Normal Concrete (NC) and Steel fiber Rice Husk Ash Concrete (SFRHAC). M25 grade of concrete using normal constituents was designed and used for referral. The RHA was used for partial replacement of Ordinary Portland Cement (OPC). The different replacement levels considered were 10, 15, 20 and 25%. It is found that workability of concrete decreased with increase in the replacement level. The optimum replacement level was found to be 15%, with respect to the compressive strength. The hooked steel fiber was added (by volume) to the RHA and Steel fiber concrete. The cubes of both NC and SFRHAC were cured in Tap water as well as in 5% Nitric acid solution till 90 days. Nitric acid is based on acid rain, sewage and industrial waste etc. The compressive strength of cubes was determined after 7, 28, 56, and 90 days. The compressive strength of water cured SFRHAC is higher than the NC. The compressive strength of both NC and SFRHAC was found to decrease in acidic solution for all the exposure periods; however, the decrease was lower in case of SFRHAC. The XRD analysis was carried out to estimate the effect of nitric acid on the constituents of concrete. The higher peaks of Calcium Silicate Hydrate (C-S-H) are detected in SFRHAC samples.